Clínica-Escola do Transtorno do Espectro Autista (CETEA): um estudo de caso no município de Cascavel (PR) - Dalmazo, Rosicleia (2023)
This research was conducted in the Clínica-Escola do Transtorno do Espectro Autista - Clinic-school of the Autistic Spectrum Disorder - (CETEA, acronym in Portuguese) Juditha Paludo Zanuzzo, opened in 2020 in the city of Cascavel (PR).The main objective of this work was to analyze the institucional work of the Clinic-School developed with autistic students and its operation. Thus, a study on Autistic Spectrum Disorder was developed, official documents were analyzed regarding the creation and operation of the clinic-school, the theoretical framework that supports the pedagogical practice and what is proposed in the school curriculum of this city was investigated (relationship between theory and practice) and the participants' view of an institution that serves exclusively autistic students in Cascavel (PR) was verified. This is theoretical and bibliographic research, based on the Cultural-Historical Psychology of Lev Semionovitch Vygotsky (1896-1934). We searched existing productions between the years 2015 and 2022 indexed in the Capes, SciELO, Google Scholar, and the Brazilian Library of Theses and Dissertations databases. However, there are only two studies on the topic (one monograph and one article). Another aspect of this study was field research, carried out through semi-structured interviews with four professionals who work at the institution and two mothers of students. Regarding the documental analysis, we considered specific documents about the creation and implementation of the clinic school, such as Decrees, Deliberations, Resolutions, and the Political-Pedagogical Project of the institution in question. As result, it was possible to verify that this is a new model of an institution in the state of Paraná, which was idealized based on the first clinic-school located in Itaboraí (RJ). Since it is a municipal educational institution, it is proposed that it follows the same curriculum; however, reality showed that there is a mismatch: while the Education sector of the clinic-school is guided by Cultural-Historical Psychology, the Health sector provides services based on Behavior Analysis and ABA therapy. It was also found that many of the actions proposed in the documents of creation and implementation of CETEA have not yet become effective, both because of the lack of hiring professionals and because of bureaucratic and administrative issues.